Clinical profile and neuroimaging of neonates with influenza encephalopathy - James, Jemila; John, Roshan Joseph; Edwin, Arun; Kailas, Lalitha; Nair, PMC (Indian Journal of Child Health, 2018)
Background: Pediatric influenza is found primarily in children under 5 years of age, and it is very difficult to distinguish the illness caused by influenza, a virus infection based on the signs alone. Objective: The objective of this study is to analyze the clinical profile and neuroimaging of neonates admitted with seizures followed by encephalopathy. Methods: A descriptive study was conducted among neonates admitted to our neonatal intensive care unit, with neurological manifestations such as poor feeding, lethargy followed by seizures and poor sensorium in the 1st week of life. During the study period, 14 neonates were included with similar neurological manifestations. Results: Our study neonates had poor feeding and lethargy (57.1%) before the onset of seizures. The mean day of the onset of seizure was day 4, and the mean duration of encephalopathy lasted for 63 h. We could detect influenza A in cerebrospinal fluid-polymerase chain reaction only in two neonates and H1N1 influenza in one neonate, but all our study neonates had consistent findings on the magnetic resonance imaging (MRI) brain suggestive of viral infection probably influenza A as its circulation in the community is considered common. The mean day of discharge from the hospital was 11.5 days. At discharge, all neonates were on breastfeeds and had no focal neurological deficit. Conclusions: The possibility of influenza A-related encephalopathy should be considered as a differential diagnosis if a neonate presents with poor feeding, lethargy followed by seizures and encephalopathy in the 1st week of life and their brain MRI